KUALITAS LAPORAN KEUANGAN BERBASIS SAK ETAP PADA KOPERASI DI KOTA TANGERANG - Triana Zuhrotun Aulia; Hamdani Hamdani (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
The purpose of this research was to examine the effect of implementing SAK ETAP on the quality of financial reports at cooperatives in Tangerang City . This study distributed 50 questionnaires and only 32 usable questionnaires. Data analysis methods used by this research were partial least square (PLS) with SmartPLS 3.0. The results of this study are implementing SAK ETAP have a positive and significant effect on the quality of financial reports. Implementation SAK ETAP proved to improve the quality of financial reports at cooperative in Tangerang City. SAK ETAP produces information is relevance, faithful representation, comparable, verifiable, timely, and understandable that is useful for users of cooperative financial reports. Keywords : implementing SAK ETAP, quality of financial reports, cooperative reports.